Clima organizacional y desempeño laboral en la Municipalidad Distrital de Huanchaco. 2017. - Mendoza Castillo, Alvaro Larry Luis Felipe (2019)
ABSTRACT The thesis work presented here had the purpose of research, determine the relationship between the organizational climate and work performance in the District Municipality of Huanchaco 2017. This research was of the type Applied with a non-experimental research design, whose target population study, was composed of 480 workers of the District Municipality of Huanchaco, the sample size is 214 workers and was obtained using the formula for finite populations. It is concluded that the relationship between the organizational climate and the labor performance of the municipality's workers in mention for the year 2017 is direct or positive with a high correlation level using Pearson's correlation of (0.95), so any attempt to improve performance goes through improving the organizational climate first. When analyzing the significance, we see that it is 3.6498E-111, that is, less than 0.05, which validates the research hypothesis. Finally, it is recommended that a shared vision be generated that is oriented towards a sustained improvement, allowing each worker to feel an important part and assume a commitment, which will allow immediate and urgent implementation of an improvement plan.